Spinal Control of Locomotion: Individual Neurons, Their Circuits and Functions - Côté, Marie-Pascale; Murray, Lynda M.; Knikou, Maria (Frontiers in Physiology, 2018)
Systematic research on the physiological and anatomical characteristics of spinal cord interneurons along with their functional output has evolved for more than one century. Despite significant progress in our understanding of these networks and their role in generating and modulating movement, it has remained a challenge to elucidate the properties of the locomotor rhythm across species. Neurophysiological experimental evidence indicates similarities in the function of interneurons mediating afferent information regarding muscle stretch and loading, being affected by motor axon collaterals and those mediating presynaptic inhibition in animals and humans when their function is assessed at rest. However, significantly different muscle activation profiles are observed during locomotion across species. This difference may potentially be driven by a modified distribution of muscle afferents at multiple segmental levels in humans, resulting in an altered interaction between different classes of spinal interneurons. Further, different classes of spinal interneurons are likely activated or silent to some extent simultaneously in all species. Regardless of these limitations, continuous efforts on the function of spinal interneuronal circuits during mammalian locomotion will assist in delineating the neural mechanisms underlying locomotor control, and help develop novel targeted rehabilitation strategies in cases of impaired bipedal gait in humans. These rehabilitation strategies will include activity-based therapies and targeted neuromodulation of spinal interneuronal circuits via repetitive stimulation delivered to the brain and/or spinal cord.